Willpower and compromise effect - Yusufcan Masatlioglu; Daisuke Nakajima; Emre Ozdenoren (Theoretical Economics, 2020)
This paper provides a behavioral foundation for the willpower as limited cognitive resource model which bridges the standard utility maximization and the Strotz models. Using the agent's ex ante preferences and ex post choices, we derive a representation that captures key behavioral traits of willpower constrained decision making. We use the model to study the pricing problem of a profit-maximizing monopolist who faces consumers with limited willpower. We show that the optimal contract often consists of three alternatives and the consumer's choices reflect a form of the "compromise effect" which is induced endogenously.
Keywords: D4; D9; 330; Willpower; compromise effect; self control; temptation; contracting